Construction of an Evaluation Index System for Consultation Competency of General Practitioners in Primary Health Care Settings Based on Leicester Assessment Package - GU Jingmei, QIN Li, ZHAO Can, PENG Houxuan, XI Qian, SHEN Ying (Zhongguo quanke yixue, 2024)
Background Training general practitioners (GPs) and improving the practice competence of "GP-centered" primary health care personnel are important directions of the development of human resources for primary health care in China. At present, there is lack of an index system applicable to evaluate clinical competence of GPs in the circumstances of primary health care in China, which not only hampers accurate identification of gaps in clinical competence of GPs, but also impedes sustainable improvement of the education and training of GPs as well as primary health care personnel. Objective To develop an evaluation index system for consultation competency of GPs in the circumstances of primary health care in China based on the original version of Leicester Assessment Package (LAP), so as to provide an index model reference for the objective evaluation of consultation competency of GPs. Methods Between May to August in 2022, a total of 15 experts were invited by using the purposive sampling method to implement the Delphi method by correspondence, to evaluate the importance, feasibility, and textual representation of each index in the initial evaluation index system for consultation competency of GPs. Analytic hierarchy process was adopted to calculate weight and combined weight for the first-level and secondary-level indexes. Results A total of two rounds of Delphi were conducted. The positivity coefficient, familiarity level, judgment coefficient, and authority coefficient were 100%, 0.77, 0.91, and 0.84 in both rounds of consultation; the mean score of the importance and feasibility of each indicator was 3.5, and the variation coefficient was 0.3. The Kendall coefficients for the importance and feasibility of the indexes in the two rounds of consultation were statistically different (P<0.001) and higher in the second round than in the first round. A total of 10 comments recommended to increase indexes, one comment to combine indexes, and 29 comments to modify indexes were collected during two rounds of Delphi consultation. The final version of evaluation system consisted of 7 first-level indexes and 42 second-level indexes, the weights of the 7 primary indicators ranged from 13.61% to 14.69%, and the combined weights of the secondary indicators ranged from 0.95% to 4.91%. Conclusion This study has constructed an evaluation index system for consultation competency of GPs in the circumstances of primary health care in China based on the original version of LAP. The evaluation index system includes 7 first-level indexes and 42 second-level indexes, which covers each essential section and important missions in GP consultations with high scientificity and practicality.